2005
DOI: 10.1238/physica.regular.072a00068
|View full text |Cite
|
Sign up to set email alerts
|

Dechanneling of Positrons in Disordered Lattices – Effect of Anharmonic Potential

Abstract: Dechanneling of positrons due to lattice disorder has been investigated for two stable configurations of the disordered face-centered cubic(fcc) lattices, Dumb-bell configuration (DBC) and Body-centered interstitial (BCI) for channeled positrons with incident energy (10–200) MeV in Cu single crystal in the planar direction (100). The effects of anharmonic terms in the channeling potential have been considered in the calculations. The calculations covered the transition-channeling probability, dechanneling prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…In previous work [7], it has been found that in harmonic approximation, the general expression of the overlap integral À 8ðe þ e 0 Þð2n þ 3Þ þ 15 e 1 þ e 0…”
Section: Transition Channeling Probability Between Two States In Two mentioning
confidence: 98%
See 1 more Smart Citation
“…In previous work [7], it has been found that in harmonic approximation, the general expression of the overlap integral À 8ðe þ e 0 Þð2n þ 3Þ þ 15 e 1 þ e 0…”
Section: Transition Channeling Probability Between Two States In Two mentioning
confidence: 98%
“…This work concentrated on such point defects by using the energetic positrons as planar channeled particles in the metal. In the case of planar channeled positrons, the transverse motion can be described by a one-dimensional Schrödinger wave equation and by solving it one can obtain transverse eigenstates and eigenvalues by using a planar potential function in harmonic oscillator approximation or a planar potential function including harmonic and higher anharmonic terms [7]. Now the planar channeled positrons in the normal region of the lattice have discrete energy states dependent on the planar potential in this region, but in the region containing point defect (disordered region) the corresponding energy states of the channeled positrons will be altered according to the type of the defect.…”
Section: Introductionmentioning
confidence: 99%
“…Here we consider the higher-order terms of power law potential for planar channeling to study anharmonic effects (10):…”
Section: Anharmonic Effectsmentioning
confidence: 99%
“…The quartic term (1/4)k 2 x 4 can be considered as a perturbation term to harmonic potential so that the modified wave function for the planar channeled positrons can be written as (10) …”
Section: Anharmonic Effectsmentioning
confidence: 99%
“…Channeling effect has found several important applications [2]. In our previous work, special consideration is devoted to the channeling of positively charged particles in disordered lattices of cubic crystals including the characteristics of channeling radiation that emits spontaneously due to transitions between eigenstates of the channeled positrons [3] in addition to calculations of the transmission and dechanneling coefficients in disordered lattices, [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%